EL PROCESO DE ABANDONO EN LA ZONA CENTRO DE CIUDAD JUÁREZ CHIHUAHUA: CASO DE ESTUDIO SECTOR LÍMITE DE CRECIMIENTO EN LA DÉCADA DE LOS SESENTAS - Terrazas, Luis Herrera (European Scientific Journal, ESJ, 2014)
The origin of the city is represented in the centers as spaces where conflicts of changes from past to present are perceived. These are places that deserve attention, to retrieve and revive, as the deterioration and neglect are linked to economic and social changes that occur in them. The implementation of strategies for the recovery and rehabilitation of these areas must be timely and specific as each center behaves and functions as its singularities. Ciudad Juarez shows abandonment processes in central areas, due to the creation of new territorial and extension areas, this is due to dynamics of commercial, industrial and housing movement. In the study area it was found this phenomenon to find a large percentage of disused buildings. On the other hand I will manage to identify the study area shows no care or intervention by the authorities for recovery, so that the loss of profitability and value in the area is increasing due to the condition of neglect and leaving it presents.